Reduction in Pavement Thickness by Using Geogrid - Vennamaneni, Sruthi; Raju Aketi, Nookapati; paisa, Sravanthi (International Journal of Engineering and Technology, 2018)
An effective way of improving the properties of naturally occurring soils for pavement construction is by using geo-synthetics. In many tropical countries, weak lateritic sub grades are common and often rejected after proof rolling during construction due to poor strength. The main aim of this research was to check the effect of geo-grid reinforcementÂ onÂ CBR value on a sample of relatively Red soil subgradeÂ under soaked and Unsoaked conditions and to Establish the effect of geogrid reinforced subgrade on the design thickness of low volume paved roads. Even though Red Soil has high strength but if we apply geogrids results going to be checked. Then by placing a layer of a Bi-axial geogrid at different heights like one layer at h/2, two layer at h/5 top and bottom ,three layers at h/6 top, bottom and middle , the effects of geogrid reinforcement on California Bearing Ratio values are investigated. This was undertaken for three strengths of geogrid and without geogrids in both soaked and Unsoaked conditions. The CBR values were used to determine the pavement thicknesses. The results indicate that the pavement thickness is reduced by 21.31% by using double layer in the Soaked condition i.e. Worse condition.Â Â